Highly siderophile element constraints on the accretion and differentiation of the Earth-Moon system - Day, J.M.D.; Pearson, D.G.; Taylor, L.A. (Science, 2007)
A new combined rhenium-osmium– and platinum-group element data set for basalts from the Moon establishes that the basalts have uniformly low abundances of highly siderophile elements. The data set indicates a lunar mantle with long-term, chondritic, highly siderophile element ratios, but with absolute abundances that are over 20 times lower than those in Earth's mantle. The results are consistent with silicate-metal equilibrium during a giant impact and core formation in both bodies, followed by post–core-formation late accretion that replenished their mantles with highly siderophile elements. The lunar mantle experienced late accretion that was similar in composition to that of Earth but volumetrically less than (0.02% lunar mass) and terminated earlier than for Earth.